THE IMPLEMENTATION CONDITIONS OF LEARNING PROGRAMS FOR MARGINALIZED GROUPS IN MEXICO AND VENEZUELA - Zhizhko, E. A. (Continuing Professional Education: Theory and Practice, 2019)
In this article are analized the implementation conditions of learning programs for marginalized groups in Mexico and Venezuela. The author found that the main categories used in the development of organizational methodological basis of professional training in Mexico and Venezuela, on the one hand, are the components of vocational education, and on the other, elements of andragogical paradigm, which should include: the “experience”, “social context training”, “selfdirected training”, “reflexive practice”, “decisions”, “realism”, “future time”, “learning cycle”. The analysis suggests include the following basic principles of training of the most vulnerable populations in Mexico and Venezuela: ensuring equality of conditions for adults with a teacher, for their motivating and giving more responsibility for their learning, strengthening their motivation and interest to achieve educational goals; development of friendly and comfortable atmosphere; providing adequate training material; relate the learning material to the past and future experiences of students; correlation theory and practice of teaching; focusing on adult autonomy in decision making; etc